COSTS TO IMPROVE MANAGEMENT SUBSTANCES IS KEPT IN ACCOUNTING - I.B.Sapayev; Z.A.Usmonov; Sh.E.Rahimova; A.B.Voxidov; D.G’.Xurramov (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
Expenses elements according to like that Grouping is the cost of producing the product to determine the structure , types to plan the size of necessary material , labor and financial continuous with resources to be provided possibility creates.